Pengaruh Lingkungan Terhadap Pendidikan Anak - Nurul Aini; Nurul Rizka Hafizah; Syahrani Syahira (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The educational environment is needed in the educational process, because the educational environment functions as a supporting the teaching and learning process. A comfortable environment will support the implementation of the teaching and learning process well. Educational environment can be divided into family environment, school environment, and community environment society. By using the literature review method, this study examines relevant theoretical sources including the relevant theoretical sources including the Quran, hadith, and recent scientific works. recent scientific works. The results show that the family environment plays as the foundation of a child's education, instilling basic values and shaping character. The school environment serves to develop academic potential, social skills and further character building. While community environment provides a practical context for the application of the values and skills that have been acquired. This study concludes that the three environments have a significant and complementary influence in shaping children's education holistically. This research recommends the importance of synergy between family, school and community in creating an optimalan optimal educational environment for children's growth and development.